CREATING ORGANIZATION DEVELOPMENT STRATEGY (World Economics and Finance Bulletin, 2023)
The following article explains the concept, content and importance of strategic management in a market economy. Effective strategic management methods in enterprises and organizations, ways to increase the effectiveness of strategic management and planning of enterprises will be studied
Keywords: enterprises; strategic management; market economy